The manufacture of knowledge : an essay on the constructivist and contextual nature of science - Knorr-Cetina, K. (Karin) (Pergamon international library of science, technology, engineering, and social studies., 1981)
The anthropological approach is the central focus of this study. Laboratories are looked upon with the innocent eye of the traveller in exotic lands, and the societies found in these places are observed with the objective yet compassionate eye of the visitor from a quite other cultural milieu. There are many surprises that await us if we enter a laboratory in this frame of mind ... This study is a realistic enterprise, an attempt to truly represent the social order of life in laboratories and institutes of research, just as they are. By bringing the philosophical issues to the surface as matter.